2018
DOI: 10.1093/jhps/hny031
|View full text |Cite
|
Sign up to set email alerts
|

What level of pain reduction can be expected up to two years after periacetabular osteotomy? A prospective cohort study of 146 patients

Abstract: Periacetabular osteotomy (PAO) corrects underlying anatomical anomalies, reduces pain and may postpone or even prevent osteoarthritis onset in patients with symptomatic acetabular dysplasia. Current evidence is based on immediate post-operative pain levels, but knowledge on pain levels in the period after PAO is scarce, and the association between pain score and acetabular angles at PAO is unknown. This study had two aims. First, we studied pain level and patient-reported outcome scores pre- and postoperativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In reviewing the literature, we observed that PROs were worse before PAO when compared to scores after PAO [ 3 , 7 , 22 , 23 , 28 , 31–39 ]. Before PAO, participants reported higher pain [ 3 , 23 , 28 , 32 , 33 , 35 , 37–40 ], worse hip-related function [ 3 , 7 , 29 , 31–47 ], lower quality of life [ 3 , 28 , 29 , 34 , 35 , 37 , 38 , 40 , 42 ], worse laboratory-based functional performance (such as walking speed) [ 32 ] and a significant reduction in PA levels, both through the use of patient-reported [ 3 , 22 , 23 , 28 , 34 , 35 , 38 , 39 , 43 , 47 , 48 ] or device-measured [ 23 , 28 ] PA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In reviewing the literature, we observed that PROs were worse before PAO when compared to scores after PAO [ 3 , 7 , 22 , 23 , 28 , 31–39 ]. Before PAO, participants reported higher pain [ 3 , 23 , 28 , 32 , 33 , 35 , 37–40 ], worse hip-related function [ 3 , 7 , 29 , 31–47 ], lower quality of life [ 3 , 28 , 29 , 34 , 35 , 37 , 38 , 40 , 42 ], worse laboratory-based functional performance (such as walking speed) [ 32 ] and a significant reduction in PA levels, both through the use of patient-reported [ 3 , 22 , 23 , 28 , 34 , 35 , 38 , 39 , 43 , 47 , 48 ] or device-measured [ 23 , 28 ] PA.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies referenced above, hip-related pain, function and quality of life were measured using common hip-related questionnaires that have been shown to be reliable and valid in individuals with hip pathology, including (i) the modified Harris Hip Score or the standard Harris Hip Score (mHHS/HHS; n = 15) [ 3 , 7 , 29 , 31–33 , 35 , 36 , 38–41 , 43 , 44 , 47 ], (ii) the Hip Disability and Osteoarthritis Outcomes Score (HOOS; n = 10) [ 3 , 29 , 32 , 35 , 37 , 38 , 40 , 42 , 43 , 46 ], (iii) the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC; n = 7) [ 33 , 35 , 38 , 39 , 44 , 46 , 47 ], (iv) the Copenhagen Hip and Groin Outcome Score (HAGOS; n = 3) [ 23 , 28 , 34 ], (v) the International Hip Outcome Tool (iHOT-12; n = 1) [ 32 ], (vi) the Patient-Reported Outcomes Measurement Information System (PROMIS; n = 1) [ 32 ], (vii) The Short Form 36 Health Survey Questionnaire (SF-36; n = 2) [ 33 , 42 ], (viii) the Numeric Pain Rating scale (NPRS; n = 1) [ 34 ], (ix) the Visual Analogue Scale (VAS; n = 1) [ 32 ], and the Non-Arthritic Hip Score (NAHS; n = 1) [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations